2017
DOI: 10.1017/s0025315417000212
|View full text |Cite
|
Sign up to set email alerts
|

Inter-annual variability in otolith chemistry of catfish Genidens barbus from South-western Atlantic estuaries

Abstract: The catfish Genidens barbus is a commercial species from South America. The aim of the present study was to examine the inter-annual variability in estuary-specific chemical signatures of otolith cores (Ba:Ca, Mg:Ca, Mn:Ca, Sr:Ca and Zn:Ca ratios) for three estuaries from Argentina and Brazil where adults were collected over multiple years. Secondarily, we evaluated whether the percentages of classification of individuals to their natal origin place are affected by the grouping of several cohorts. Most element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…Description of growth parameters using length and age data (Velasco et al, 2007) and the use of estuarine carbon sources revealed by isotope analyses (Pereyra et al, 2016) report biological aspects for the species. Ecological aspects were revealed by otolith microchemistry and patterns of estuarine uses (Avigliano et al, 2015), inter-annual variability (Avigliano et al, 2017a), freshwater residence times (Avigliano et al, 2017b), nursery grounds and connectivity (Avigliano et al, 2016) are available for the species.…”
Section: Babitonga Bay Estuary: South Brazil/subtropicalmentioning
confidence: 99%
“…Description of growth parameters using length and age data (Velasco et al, 2007) and the use of estuarine carbon sources revealed by isotope analyses (Pereyra et al, 2016) report biological aspects for the species. Ecological aspects were revealed by otolith microchemistry and patterns of estuarine uses (Avigliano et al, 2015), inter-annual variability (Avigliano et al, 2017a), freshwater residence times (Avigliano et al, 2017b), nursery grounds and connectivity (Avigliano et al, 2016) are available for the species.…”
Section: Babitonga Bay Estuary: South Brazil/subtropicalmentioning
confidence: 99%
“…Annuli were counted in transmitted light using a stereomicroscope (Leica® EZ4-HD, Singapore) at 40X magnification while otoliths were immersed in ultrapure water. In terms of age criteria, the protocol previously reported by Avigliano et al (2017a) for G. barbus was used to ageing the specimens. Mean age ± SD and range (in years) were 7.3 ± 1.17 (6-10) for PEC, 9.5 ± 0.97 (7-10) for PRD, for NR.…”
Section: Fish Agingmentioning
confidence: 99%
“…There has been considerable research on the geographical variation of natal geochemical signatures, but limited studies have examined the temporal stability of otolith chemistry. Studies that examined temporal variation in otolith chemical composition found substantial variations within (Thorrold and Shuttleworth 2000;Reis-Santos et al 2012) and among years (Campana et al 2000;Gillanders 2002;Walther and Thorrold 2009;Pruell et al 2012), which could lead to misinterpretation of spatial variability in otolith signatures (Reis-Santos et al 2012;Avigliano et al 2018). For instance, in Platichthys flesus (Linnaeus, 1758) and Dicentrarchus labrax (Linnaeus, 1758), collected from several estuaries along the Portuguese coast in two years and three seasons within a year, significant differences were observed in the majority of otolith elements among estuaries and sampling times, which were likely to be a reflection of the observed variability in environmental conditions, incorporating seasonal variation, which resulted in an 11% increase in the correct classification of individual estuaries (Reis-Santos et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There was some overlap in elemental fingerprints among years for different estuaries for juvenile snapper Pagrus auratus (Forster, 1801), which was likely to have consequences in the assignment of adult fish to recruitment estuaries, especially if juvenile fish were collected from different estuaries in different years and adult fish were not assigned to recruitment estuaries using elemental fingerprints from the year class of recruits in which they were juveniles (Gillanders 2002). Furthermore, the long-term stability of otolith chemical signatures has been less frequently investigated (Avigliano et al 2018), suggesting that chemical signatures may serve only as shortterm natural tags (1-3 y) (Rooker et al 2001;Walther and Thorrold 2009;Pruell et al 2012).…”
Section: Introductionmentioning
confidence: 99%